2021
DOI: 10.3390/brainsci11111486
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Locus Coeruleus Complex—Consistencies and Variances in Nuclear Organization

Abstract: Descriptions of the nuclear parcellation of the locus coeruleus complex have been provided in approximately 80 mammal species spanning the phylogenetic breadth of this class. Within the mammalian rostral hindbrain, noradrenergic neurons (revealed with tyrosine hydroxylase and dopamine-ß-hydroxylase immunohistochemistry) have been observed within the periventricular grey matter (A4 and A6 nuclei) and parvicellular reticular nucleus (A5 and A7 nuclei), with the one exception to date being the tree pangolin, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 71 publications
0
18
0
1
Order By: Relevance
“…We did not verify the subcellular localization, but the functional effects of DCZ injection indicates that a sufficient amount of hM4Di receptors was present in the membrane of LC neurons to respond to DCZ. Lastly, even if the coverage of LC neurons seemed relatively homogenous, this remains difficult to assess given the anatomical heterogeneity of the nucleus in monkeys [ 13 , 35 ]. Even if a finer characterization of that heterogeneity would be critical to better understand the specific functions of LC in primates, we believe that the current method is sufficient to induce a reliable activation of LC neurons, and along with a finer anatomical characterization of the effects, further functional testing would also be critical to evaluate its efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not verify the subcellular localization, but the functional effects of DCZ injection indicates that a sufficient amount of hM4Di receptors was present in the membrane of LC neurons to respond to DCZ. Lastly, even if the coverage of LC neurons seemed relatively homogenous, this remains difficult to assess given the anatomical heterogeneity of the nucleus in monkeys [ 13 , 35 ]. Even if a finer characterization of that heterogeneity would be critical to better understand the specific functions of LC in primates, we believe that the current method is sufficient to induce a reliable activation of LC neurons, and along with a finer anatomical characterization of the effects, further functional testing would also be critical to evaluate its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of pharmacogenetics has allowed key advances in understanding neuromodulatory functions [ 10 , 11 , 12 ]. Indeed, pharmacogenetics allow researchers to reversibly and reliably manipulate the activity of entire populations of neurons, with a high level of specificity [ 13 ]. The development of this approach in monkeys is critical for several reasons: First, it allows us to study behavioral and cognitive processes (and corresponding brain regions) that relay upon brain regions that are specific to primates [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neurophysiological research on rodents and nonhuman primates has identified the LC-NE as the center of the mammalian arousal system [25,[38][39][40] and as being important for determining levels of wakefulness [41][42][43]. In contrast, the LC-NE has largely been regarded as unable to modulate activity in attention relevant specific cortical networks [5].…”
Section: Introductionmentioning
confidence: 99%
“…The locus coeruleus (LC) is a vertebrate-specific norepinephrinergic (NE) nucleus [ 1 , 2 , 3 , 4 ]. The LC locates deeply in the dorsal part of the brainstem [ 5 ], where a small number of neurons extensively branch their axons and provide the main source of NE to the brain [ 6 ].…”
Section: Introductionmentioning
confidence: 99%